Harnessing Localized Ridges for High‐Aspect‐Ratio Hierarchical Patterns with Dynamic Tunability and Multifunctionality. (12th December 2013) - Cao, Changyong; Chan, Hon Fai; Zang, Jianfeng; Leong, Kam W.; Zhao, Xuanhe
<x xml:space="preserve">Abstract</x> A simple method for fabricating high‐aspect‐ratio, hierarchical, and dynamically tunable surface patterns is invented by harnessing localized‐ridge instabilities in gold nanofilms coated on elastomer substrates (a); a theoretical model to calculate the critical parameters (e.g., wavelength and amplitude) for designing the new patterns is developed (b); and novel applications of the patterns as super‐hydrophobic coatings (c) and biomimetic cell‐culture substrates (d) capable of on‐demand tunability are demonstrated. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>